High‐resolution hippocampal diffusion tensor imaging of mesial temporal sclerosis in refractory epilepsy. Issue 9 (25th June 2022) - Chau Loo Kung, Gustavo; Chiu, Andrew; Davey, Zach; Mouchawar, Nicole; Carlson, Mackenzie; Moein Taghavi, Hossein; Martin, Douglas; Graber, Kevin; Razavi, Babak; McNab, Jennifer; Zeineh, Michael
Abstract: Objective: We explore the possibility of using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) to discern microstructural abnormalities in the hippocampus indicative of mesial temporal sclerosis (MTS) at the subfield level. Methods: We analyzed data from 57 patients with refractory epilepsy who previously underwent 3.0‐T magnetic resonance imaging (MRI) including DTI as a standard part of presurgical workup. We collected information about each subject's seizure semiology, conventional electroencephalography (EEG), high‐density EEG, positron emission tomography reports, surgical outcome, and available histopathological findings to assign a final diagnostic category. We also reviewed the radiology MRI report to determine the radiographic category. DTI‐ and NODDI‐based metrics were obtained in the hippocampal subfields. Results: By examining diffusion characteristics among subfields in the final diagnostic categories, we found lower orientation dispersion indices and elevated axial diffusivity in the dentate gyrus in MTS compared to no MTS. By similarly examining among subfields in the different radiographic categories, we found all diffusion metrics were abnormal in the dentate gyrus and CA1. We finally examined whether diffusion imaging would better inform a radiographic diagnosis with respect to the final diagnosis, and found that dentate diffusivity suggested subtle changes that may help confirm a positive radiologic diagnosis. Significance: The results suggest that diffusion metric analysis at the subfield level, especially in dentate gyrus and CA1, maybe useful for clinical confirmation of MTS.